Integrated Bioinformatics and Experimental Approaches Identified the Role of NPPA in the Proliferation and the Malignant Behavior of Breast Cancer - Aijun Sun; Xiaonan Sheng; Jinhai Tang; Zhenfeng Yu; Jian Zhang (Journal of Immunology Research)
Breast cancer is the 3rd most common type of malignant tumor worldwide with high heterogeneity, frequent recurrence, and high metastasis tendency. In this study, we aimed to demonstrate the value of extracellular matrix- (ECM-) related genes in breast cancer patients. The overall expression of ECM is assessed with a novel SC3 clustering method, and patients were divided into two clusters with diverse recurrence rate. We established the Cox regression model in breast cancer patients and identified NPPA as an independent prognostic marker. The NPPA expression is downregulated in breast cancer patients, independent of the ER status, PR status, stemness score, and immune infiltrating condition. And we observed the enhanced proliferation, migration, and invasion potential of breast cancer cells after NPPA depletion. Further, we predicted the transcription modulation of NPPA with PROMO and JASPAR. And we further validated the binding of MZF1 to the -318 bp~-452 bp region of the NPPA promoter with chromatin immunoprecipitation and dual luciferase assay. Together, our study identified NPPA as a potential prognostic biomarker for breast cancer patients, whose downregulation is associated with an enhanced malignant behavior of breast cancer cells both in vivo and in vitro and identified the transcription regulation of NPPA by MZF1.